2004
DOI: 10.1111/j.1399-3054.2004.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular localization of a lipid transfer protein in Vigna unguiculata seeds

Abstract: Lipid transfer proteins (LTP) facilitate transfer of lipids between membranes in vitro. Up to now, they have been found to be localized basically in the plant cell wall and in compartments linked to lipid metabolism, such as glyoxysomes. Accordingly, LTP are considered to be involved in the plant defence against pathogen microbes and lipid metabolism. We herein show, by immunoelectron microscopy, that besides the cell wall, LTP are localized in the lumen of organelles which we suggest to be the protein storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…In addition, LTPs contain a signal peptide at the N terminus, generally 21 to 27 amino acids for the LTP1 family and 27 to 35 amino acids for the LTP2 family (Carvalho and Gomes, 2007), allowing mature LTP peptides to enter the secretory pathway. Consistently, several LTP1 members from Arabidopsis (Thoma et al, 1993), Brassica oleracea var italica (Pyee et al, 1994), Ricinus communis (Tsuboi et al, 1992), and Vigna unguiculata (Carvalho et al, 2004) are localized at the cell wall, while the extracellular localization of these LTPs was not in line with the assumed function of these proteins in cell cytoplasm (Carvalho and Gomes, 2007).…”
mentioning
confidence: 92%
“…In addition, LTPs contain a signal peptide at the N terminus, generally 21 to 27 amino acids for the LTP1 family and 27 to 35 amino acids for the LTP2 family (Carvalho and Gomes, 2007), allowing mature LTP peptides to enter the secretory pathway. Consistently, several LTP1 members from Arabidopsis (Thoma et al, 1993), Brassica oleracea var italica (Pyee et al, 1994), Ricinus communis (Tsuboi et al, 1992), and Vigna unguiculata (Carvalho et al, 2004) are localized at the cell wall, while the extracellular localization of these LTPs was not in line with the assumed function of these proteins in cell cytoplasm (Carvalho and Gomes, 2007).…”
mentioning
confidence: 92%
“…AlLTPs from Allium species are localized in endomembrane compartments (Yi et al, 2009), while a LTP in germinating sunflower seeds was found in both intracellular and extracellular localizations (Pagnussat et al, 2009). Moreover, a LTP from castor bean (Ricinus communis) was localized in the glyoxysome matrix (Tsuboi et al, 1992), and a LTP from Vigna unguiculata seeds in the protein storage vacuoles (Carvalho et al, 2004). Another exception is the apparent chloroplast localization of RlemLTP, a rough lemon nsLTP with antifungal activity against Alternaria alternata and Fusarium oxysporum.…”
Section: Introductionmentioning
confidence: 97%
“…In the last years, several proteins such as trypsin and papain inhibitors (Xavier-Filho et al 1989), variant vicilins (7S globulin storage proteins) , glucan hydrolases represented by chitinases and b-1,3-glucanase (Gomes et al 1996), antimicrobial peptides identified as lipid transfer proteins (LTP) and defensins (Carvalho et al 2001(Carvalho et al , 2004 were found in seeds of cowpea. These proteins are commonly linked to plant defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%